OCP Exam 1Z0-063 - Freeman, Robert G. 1965- (Wiley, 2014)
An updated guide for an updated certification exam! As the most popular database software in the world, Oracle Database 12c has been updated for the first time in nearly six years and the changes are significant. This study guide reviews how Oracle 12c allows multiple instances to be used simultaneously via the cloud. You'll sharpen your skills to prepare for the three levels of certification: Oracle Certified Associate, Oracle Certified Professional, and Oracle Certified Master. Workbook exercise appendix, test engine, chapter review questions, electronic flashcards, searchable PDF glossary, and two bonus practice exams all help to enhance your preparation to take the Oracle 12c exam. Addresses such topics as: database architecture, configuring and recoverability, configuring backup specifications, and performing user-managed backup and recovery Reviews how to use RMAN to create backups, perform recovery, and duplicate a database Looks at performing tablespace point-in-time recovery and using flashback technology Covers diagnosing the database, managing memory, managing resources, and automating tasks Focusing 100 percent on the exam objectives, OCP: Oracle Database 12c Administrator Certified Professional Study Guide is designed for those who feel they are ready to attempt this challenging exam